Fluopyram induces behavioural, hepatotoxic and metabolic alterations in fish at environmentally relevant concentrations - Lucie Bouly; Lisa Jacquin; Séverine Paris-Palacios; Camille Pasquet; Jean-Marc Bonmatin; Océane Delos; Lara Galès; Justine Bertrand-Michel; Floriant Bellvert; Marion Vivant; Pascal Laffaille; Anthony Lemarié; et al. (Journal of Hazardous Materials, 2026)

Spatio‐temporal dynamics of Allis shad ( Alosa alosa L .) spawning in response to environmental variability - Pauline Ladoux; Marion Legrand; Cédric Briand; Laëtitia Buisson; Pascal Laffaille (Journal of Fish Biology, 2026)
The Allis shad ( Alosa alosa L.) is a threatened anadromous fish species whose populations have dramatically declined in recent decades due to multiple anthropogenic pressures, including habitat fragmentation, water quality degradation and overexploitation. In this study, we aimed (1) to identify the environmental and spatio‐temporal drivers of spawning probability and intensity, and (2) to estimate the number of spawners over time in two major French river catchments, the Garonne and the Loire. Using generalized additive models, we found that these models performed well in predicting spawning dynamics. Spawning probability and intensity were significantly influenced by environmental variables (temperature, discharge and precipitation) and spatio‐temporal factors (sampling site, river catchment, year and Julian day). Specifically, moderate increases in temperature during the pre‐spawning period and low to moderate discharge on the day before or the day of spawning were associated with higher spawning probabilities and greater spawning intensity. In contrast, a temperature decrease a few days before spawning, excessively low or high discharge on the day before or the day of spawning and excessive precipitation on the spawning day were associated with lower spawning probability and intensity. Additionally, trends in the estimated number of spawners at spawning sites between 2001 and 2022 revealed a significant severe decline in both river catchments, with an average population decrease of approximately 90% in the Garonne and 75% in the Loire. These findings highlight the critical situation and the urgent need for management measures to mitigate the ongoing decline of Allis shad populations.

Synchrony between reproductive patterns and photoperiod in Allis shad (Alosa alosa L.) in the Loire River catchment - Pauline Ladoux; Marion Legrand; Pierre Portafaix; Laëtitia Buisson; Pascal Laffaille (Aquatic Ecology, 2025)

Adaptive plastic responses to metal contamination in a multistress context: a field experiment in fish - Quentin Petitjean; Pascal Laffaille; Annie Perrault; Myriam Cousseau; Séverine Jean; Lisa Jacquin (Environmental Science and Pollution Research, 2023)

Combined effects of temperature increase and immune challenge in two wild gudgeon populations - Quentin Petitjean; Séverine Jean; Jessica Côte; Amaïa Lamarins; Marie Lefranc; Raphaël Santos; Annie Perrault; Pascal Laffaille; Lisa Jacquin (Fish Physiology and Biochemistry, 2020)

Consumer trophic positions respond variably to seasonally fluctuating environments - Bailey C. McMeans; Taku Kadoya; Thomas K. Pool; Gordon W. Holtgrieve; Sovan Lek; Heng Kong; Kirk Winemiller; Vittoria Elliott; Neil Rooney; Pascal Laffaille; Kevin S. McCann (Ecology, 2019)
The effects of environmental seasonality on food web structure have been notoriously understudied in empirical ecology. Here, we focus on seasonal changes in one key attribute of a food web, consumer trophic position. We ask whether fishes inhabiting tropical river–floodplain ecosystems behave as seasonal omnivores, by shifting their trophic positions in relation to the annual flood pulse, or whether they feed at the same trophic position all year, as much empirical work implicitly assumes. Using dietary data from the Tonle Sap Lake, Cambodia, and a literature review, we find evidence that some fishes, especially small piscivores, increased consumption of invertebrates and/or plant material during the wet season, as predicted. However, nitrogen stable isotope (δ 15 N) data for 26 Tonle Sap fishes, spanning a broader range of functional groups, uncovered high variation in seasonal trophic position responses among species (0 to ±0.52 trophic positions). Based on these findings, species respond to the flood pulse differently. Diverse behavioral responses to seasonality, underpinned by spatiotemporal variation at multiple scales, could be central for rerouting matter and energy flow in these dynamic ecosystems. Seasonally flexible foraging behaviors warrant further study given their potential influence on food web dynamics in a range of fluctuating environments.

Multistress effects on goldfish (Carassius auratus) behavior and metabolism - Allison Gandar; Séverine Jean; Julie Canal; Nathalie Marty-Gasset; Franck Gilbert; Pascal Laffaille (Environmental Science and Pollution Research, 2016)

Measurements of spatial population synchrony: influence of time series transformations - Mathieu Chevalier; Pascal Laffaille; Jean-Baptiste Ferdy; Gaël Grenouillet (Oecologia, 2015)

A cost-effective method to quantify biological surface sediment reworking - Eve De Nadaï-Monoury; Antoine Lecerf; Julie Canal; Laëtitia Buisson; Pascal Laffaille; Franck Gilbert (Hydrobiologia, 2013)

Toward a loss of functional diversity in stream fish assemblages under climate change - Laëtitia Buisson; Gaël Grenouillet; Sébastien Villéger; Julie Canal; Pascal Laffaille (Global Change Biology, 2013)
The assessment of climate change impacts on biodiversity has so far been biased toward the taxonomic identification of the species likely either to benefit from climate modifications or to experience overall declines. There have still been few studies intended to correlate the characteristics of species to their sensitivity to climate change, even though it is now recognized that functional trait‐based approaches are promising tools for addressing challenges related to global changes. In this study, two functional indices (originality and uniqueness) were first measured for 35 fish species occurring in French streams. They were then combined to projections of range shifts in response to climate change derived from species distribution models. We set out to investigate: (1) the relationship between the degrees of originality and uniqueness of fish species, and their projected response to future climate change; and (2) the consequences of individual responses of species for the functional diversity of fish assemblages. After accounting for phylogenetic relatedness among species, we have demonstrated that the two indices used measure two complementary facets of the position of fish species in a functional space. We have also rejected the hypothesis that the most original and/or less redundant species would necessarily experience the greatest declines in habitat suitability as a result of climate change. However, individual species range shifts could lead simultaneously both to a severe decline in the functional diversity of fish assemblages, and to an increase in the functional similarity among assemblages, supporting the hypothesis that disturbance favors communities with combination of common traits and biotic homogenization as well. Our findings therefore emphasize the importance of going beyond the simple taxonomic description of diversity to provide a better assessment of the likely future effects of environmental changes on biodiversity, thus helping to design more effective conservation and management measures.

Are amphipod invaders a threat to regional biodiversity? - Christophe Piscart; Benjamin Bergerot; Pascal Laffaille; Pierre Marmonier (Biological Invasions, 2010)

Habitat preferences of different European eel size classes in a reclaimed marsh: A contribution to species and ecosystem conservation - Pascal Laffaille; Aurore Baisez; Christian Rigaud; Eric Feunteun (Wetlands, 2004)

European salt marshes diversity and functioning: The case study of the Mont Saint-Michel bay, France - Jean-Claude Lefeuvre; Virginie Bouchard; Eric Feunteun; Sonia Grare; Pascal Laffaille; Alain Radureau (Wetlands Ecology and Management, 2000)

Do fish communities function as biotic vectors of organic matter between salt marshes and marine coastal waters? - Jean-Claude Lefeuvre; Pascal Laffaille; Eric Feunteun (Aquatic Ecology, 1999)

Role of fish communities in particulate organic matter fluxes between salt marshes and coastal marine waters in the Mont Saint-Michel Bay - Pascal Laffaille; Sébastien Brosse; Eric Feunteun; Aurore Baisez; Jean-Claude Lefeuvre (Hydrobiologia, 1998)